(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Childhood cancer imposes considerable financial burden for the family which ultimately leads to serious economic consequences for the family. Families have to cope up these costs by adopting various strategies. Objective: To determine the strategies to mitigate financial burden of childhood cancer. Materials and Methods: This cross sectional study was conducted among 220 childhood cancer patients at selected specialized hospitals of Bangladesh. Face-to-face interview of the parents or guardian with semi-structured questionnaire following systematic random sampling technique data were collected. Results: Mean age of the children was 7.30±4.203 years and majority (66.4%) was male. Most of them (78.6%) were from rural and average monthly family income was BDT 11634.09±8740.630. Among all the children majority (39.1%) had leukaemia followed by blastoma (28.2%), sarcoma (15.9%), lymphoma (10.0%) and adenocarcinoma (6.8%). Average treatment cost was BDT 45593.59±12187.637. Sources of fund for treatment included were from family savings (35.9%), loan (70.5%), receiving donation (56.8%), support from relatives (75.0%) and property selling (59.5%). Strategies adopted by parents to overcome the situation all (100%) of them accepted as reality and started various religious activities it also included changing life style (94.5%), taking social support (54.1%) and minimizing family investment (22.3%). Conclusion: Childhood cancer is a growing public health problem in Bangladesh, so different cost effective measures like subsidized or free of cost treatment should be adopted to reduce the financial burden of the families of the victims of childhood cancer. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 25-28